Menyelisik Shadow Economy Di Indonesia - Rastri Paramita (Pusat Kajian Anggaran, 2020)
The purpose of this study is to know the relationship between economic growth and the shadow economy through the transmission of labor conditions as well as to know the effect of the shadow economy on tax revenue in Indonesia. This study uses a qualitative method to find out the issue. The results of this study show that the development of the shadow economy and economic growth in Indonesia in the 2000-2015 period tends to fluctuate and the relationship between economic growth and the shadow economy is not always negative. However, in the last 16 years, the shadow economy's percentage of GDP has decreased. Meanwhile, the connection between the shadow economy and tax revenue in Indonesia, namely the simplification of the bureaucracy in starting a business in Indonesia, is expected to have a greater impact on reducing shadow economy growth. To slow down the shadow economy growth caused by bureaucracy, the Directorate General of Taxes (DGT) needs to take tactical steps by making improvements and innovating tax services, from online registration of NPWP to launching a single login with innovation allowing taxpayers to access various tax services at one-time log-in, and cooperation in exchanging information to minimize the presence of asymmetrical information between the DGT and taxpayers, accompanied by tax incentives for taxpayers who wish to share information.